Diversity of macroalgae in the intertidal zone of Iboih Beach, Sabang, Indonesia - Suwarniati Suwarniati; Maria Ulfa; Meutia Zahara; Nurul Fajriana; Muslim Amiren; Qurratu Aini (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
The intertidal zone of Iboih Beach in Sukakarya District, Sabang, has significant macroalgae diversity with different substrate variations. This study examined the diversity, distribution, and ecological significance of macroalgae using the quadrat method with purposive sampling technique on three plots measuring 2 2 m (coral, sand, and rock substrates), each replicated three times. Measurements of environmental parameters including temperature (using a thermometer), salinity (refractometer), and depth (Secchi disk) were carried out prior to sampling to ensure that environmental conditions were recorded. The results showed Galaxaura rugosa as the dominant species (INP 63.22), followed by Halimeda opuntia (38.42) and Chaetomorpha crassa (35.27), which showed a preference for hard substrates rich in nutrients. In contrast, Caulerpa sp. had the lowest INP (9.33), indicating specific habitat adaptation. The Shannon-Wiener diversity index (H=1.57) was in the moderate category, with an average INP of 28.575 reflecting a diverse community occupying different ecological niches. The coral substrate supported the highest abundance due to its stability and nutrient availability. This finding confirms the crucial role of substrate characteristics in the structure of intertidal macroalgal communities.Keywords:DiversityMacroalgaeIntertidal zoneSubstrateIboih Beach